Product design. - Asensio, Paco, ....- (New York : teNeues, 2002)
P.10.Introduction p.20.History p.42.Packaging p.54.The design process p.60.Current trends p.72.In p.74.Office p.118.Tools p.142.Electrical appliances p.162.Furniture p.200.Kitchen p.236.Bathroom p.264.Out p.266.Complements p.302.Urban furniture p.336.Leisure p.368.Vehicles p.396.Directory
Keywords: Fabricage; Ontwerpen; Productontwikkeling